Moralitas di Dunia Maya: Hukum Mengemis Online Live Tik Tok dalam Perspektif Al-Ghazali - Nuraini; Nasrulloh; Latifah, Hamidatul; Qurrota Ayuni, Rizka; Kastrawi, Puji (State of Islamic Institute Langsa, 2024)
The rise of controversy programs on live Tik Tok is very detrimental to various parties. One of them is the trend of begging online to generate massive rupiah coffers. Open-access digital platforms should require users to be careful because they become public consumption. In fact, this application is used to beg openly and even display the user's name and face. This study aims to analyze the phenomenon of online begging from the live Tik Tok perspective of Imam Al Ghazali. This research method is qualitative research with a focus on literature research. The data analysis used in this study is descriptive qualitative analysis. The result is that begging online is haram because it is deceitful and takes advantage of certain circumstances to get as many gifts as possible. This is evidenced by the aqli arguments about begging, the impact of online begging on live Tik Tok, and Imam Al Ghazali's perspective regarding begging.